PUBLIC POLICIES TO SUPPORT SMES’ ACCESS TO FINANCING: BETWEEN CHALLENGES OF CRISES AND THE FUNCTIONING OF MARKETS - Ioana-Carmen BOZINTAN (COSMA-GULER); Daniel BADULESCU (Annals of the University of Oradea: Economic Science)
Access to finance for small and medium-sized enterprises has been identified in many studies as the most important factor determining the survival and growth of SMEs in both developing and developed countries. Access to financing means access to working capital to finance current activity, but also investments and the acquisition of modern technologies, thus ensuring the competitiveness of SMEs, as well as the performance of the economy and society as a whole. Governments, through specialized agencies, often in cooperation with financial regulatory authorities and banking associations, develop various measures and programs aimed at better access to finance for SMEs. Of course, the motivations, scope and success of these initiatives are influenced by the level of development and sophistication of the financial banking sector, by its orientation and composition, by the way in which the various objectives and needs of small and medium businesses are understood. The implementation and prioritization of these programs and schemes are dramatically influenced by the availability of financial and non-financial resources, organizational skills and, finally, the sincerity and stability of dedicated public policies. This paper aims to analyze the impact of financial support policies for SMEs, the effects of crises (economic, financial, pandemic) on these policies, but also the evolution of interest in this type of support at the level of European companies. We found that government financial assistance helps SMEs to improve their financial performance and thus be able to access, in the future, various forms of financing, but also that there are significant differences, by activity sectors, types of companies and, respectively, countries, in regarding the importance and impact of public support to the business sector.